Accuracy of low-field magnetic resonance imaging for differentiating intervertebral disc extrusions and protrusions at the lumbosacral disc space in dogs - Shing, Hannah; Caine, Abby; Cherubini, Giunio Bruto; Sparks, Tim; Housley, Daniel (Frontiers in Veterinary Science, 2023)
Introduction/Purpose: MRI features differentiating extrusion from protrusion in thoracolumbar discs have been published, however little specifically evaluates the lumbosacral disc. The high prevalence of degenerative changes in apparently normal animals complicates assessment of this region and features relevant elsewhere in the spine may not apply. The aims of this study were to determine the accuracy of MRI in differentiating IVDE and IVDP at the lumbosacral disc space in dogs and determine which MRI characteristics discriminate between IVDE and IVDP.Method: MRI examinations from dogs with surgically confirmed IVDE or IVDP at the lumbosacral disc space were collected retrospectively (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019). Two radiologists independently recorded a diagnosis of IVDE or IVDP, gave a confidence rating, and evaluated specific MRI features. Univariable statistical analysis was performed to identify which MRI characteristics might help distinguish IVDE from IVDP.Results: 117 dogs with lumbosacral IVDE (n = 16) or IVDP (n = 101) were included. Features associated with IVDE were in concordance with previous studies and included interruption of the dorsal annulus, suspected epidural hemorrhage, dispersed (rather than confined) intervertebral disc herniation on T2W sagittal images, lateralized intervertebral disc herniation and displacement of the cauda equina. Overall diagnostic accuracy was 68.8% and interobserver agreement was fair (k = 0.37), which is lower than has been reported in thoracolumbar disc herniation, but accuracy increased to 85.3% and substantially improved agreement (k = 0.87) in "confident" diagnoses.Discussion/Conclusion: MRI characteristics used in differentiating thoracolumbar IVDE and IVDP can be extrapolated to the lumbosacral intervertebral disc space, but diagnostic accuracy in low-field MRI is lower than previously reported in herniations involving the thoracolumbar spine.